Factor II, VII, IX and X concentrations in patients receiving long term warfarin. Issue 1 (January 1987) - Paul, B; Oxley, A; Brigham, K; Cox, T; Hamilton, P J
Abstract : Using standard one stage clotting assays the concentrations of factors II, VII, IX and X were determined in 37 patients stabilised on warfarin for between three months and 17 years. Contrary to popular belief, the concentrations were not equally depressed, with factor X the lowest, factor II at intermediate value, factors VII and IX the highest. Some 71% of the variance of the British corrected ratio (BCR) could be accounted for by measurement of the factors assayed. Analysis of this variance showed 91% of the explained variance attributable to factor II, 7% to factor VII, 1.6% to factor IX and 0.4% to factor X. With the sudden and recent withdrawal of human thromboplastin, investigation of the sensitivities of the animal thromboplastins to changes in vitamin K dependent factors in orally anticoagulated patients is needed to ensure that the potentially alarming falls in factors II and X in these patients are being adequately detected.